Wind characteristics analysis and application of ontrol strategy for wind system based on direct power control - Bedoud Khouloud; Bahi Tahar; Merabet Hichem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This study analyses yearly and seasonal wind speed data recorded over eight years using Weibull distribution function and the direct power control application of a wind chain. The wind potential evaluation was carried out based on empirical model. Results show that, during the warm months the wind speed is uniform, constant and stable. In addition, it has been found that the use of a control strategy was necessary for extracting the optimum power. For this purpose, the second part of this work presents a direct power control (DPC) technique in order to adjust the produced active and reactive powers. The application and performance evaluation of the proposed control system implemented within the d-q reference framework has been exposed and discussed. The system modeling and the control diagram are built under MATLAB software. According to simulation results, the forward power control provides almost sinusoidal input waveform current, constant switching frequency operation, unity power factor regulation and also provides powers decoupling. As shown by simulation results, the suggested control method is efficient.